1999
DOI: 10.1016/s0014-5793(99)00446-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of cytoplasmic signalling molecules SHP‐1, SHP‐2, SHIP and phospholipase C‐γ1 with PECAM‐1/CD31

Abstract: Recent studies have shown that, in addition to its role as an adhesion receptor, platelet endothelial cell adhesion molecule 1/CD31 becomes phosphorylated on tyrosine residues Y 663 and Y 686 and associates with protein tyrosine phosphatases SHP-1 and SHP-2. In this study, we screened for additional proteins which associate with phosphorylated platelet endothelial cell adhesion molecule 1, using surface plasmon resonance. We found that, besides SHP-1 and SHP-2, platelet endothelial cell adhesion molecule 1 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 33 publications
2
74
0
Order By: Relevance
“…23 Phosphorylation of these two tyrosine residues in PECAM-1 creates docking sites for the binding and activation of several cytosolic signaling molecules containing src homology-2 (SH2) domains. Included among the SH2-containing molecules that associate with PECAM-1 are the protein tyrosine phosphatases, SHP-1 and SHP-2, [24][25][26][27][28][29][30][31] the inosital phosphatase, SHIP 31 and phospholipase C-γ. 31 PECAM-1 may also associate with phosphoinositide 3-kinase 32 and β-or γ-catenin.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…23 Phosphorylation of these two tyrosine residues in PECAM-1 creates docking sites for the binding and activation of several cytosolic signaling molecules containing src homology-2 (SH2) domains. Included among the SH2-containing molecules that associate with PECAM-1 are the protein tyrosine phosphatases, SHP-1 and SHP-2, [24][25][26][27][28][29][30][31] the inosital phosphatase, SHIP 31 and phospholipase C-γ. 31 PECAM-1 may also associate with phosphoinositide 3-kinase 32 and β-or γ-catenin.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Included among the SH2-containing molecules that associate with PECAM-1 are the protein tyrosine phosphatases, SHP-1 and SHP-2, [24][25][26][27][28][29][30][31] the inosital phosphatase, SHIP 31 and phospholipase C-γ. 31 PECAM-1 may also associate with phosphoinositide 3-kinase 32 and β-or γ-catenin. 33,34 The ability of PECAM-1 to bind to these various cytosolic molecules enables it to potentially modulate the activity of a number of intracellular signaling pathways.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…The PECAM-1 cytoplasmic domain contains two immunoreceptor tyrosine-based inhibitory motifs (ITIMs) centered around Tyr663 and Tyr686 that become phosphorylated in response to a variety of cellular activation events, after which they are able to recruit a number of Src homology 2 (SH2) domain-containing cytosolic signaling molecules, the best known of which is the protein-tyrosine phosphatase SHP-2 (Newman and Newman, 2003). Other SH2 domain-containing proteins that have been reported to associate with PECAM-1 include SHP-1 (Cao et al, 1998;Henshall et al, 2001;Hua et al, 1998;Pumphrey et al, 1999;Sagawa et al, 1997), Src family kinases (Lu et al, 1997;Masuda et al, 1997;Osawa et al, 1997), the inositol 5Ј-phosphatase SHIP-1 (Pumphrey et al, 1999) and phospholipase C1 (Henshall et al, 2001;Pumphrey et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A ITSM-like motif is situated 3-7 residues from the C terminus and is preceded by a conventional ITIM motif. Interestingly, similar to CD150ct, a GST platelet endothelial cell adhesion molecule/ CD31 cytoplasmic tail can bind both SHP-2 and SHIP, and SHIP interacts predominantly with the ITSM motif in CD31 (43).…”
Section: Modeling Of the Cd150ctmentioning
confidence: 99%
“…Using our model and SHP-2 structure revealed by crystallography (49), we predicted that simultaneous binding of Y281 and Y327 by two SHP-2 SH2 domains is unlikely, because the distance between tyrosine-binding pockets of N-and C-terminal domains of SHP-2 is 40 Å, compared with 8.18 Å, between Y281 and Y327 residues in CD150ct model. Moreover, it was shown that only the N-SH2, but not the C-SH2 domain of SHP-2 phosphopeptides binds to both ITIM-and ITSM-like motifs of CD31 (43).…”
Section: Modeling Of the Cd150ctmentioning
confidence: 99%